Internacionalização de empresas trading japonesas: uma análise da estrutura de propriedade sob a ótica do tripé estratégico - Passos, Denner Honda (2022)
The international business literature posits that adopting a global approach to strategy is necessary for multinational enterprises (MNEs) to maintain or increase their competitive advantages, particularly in the manufacturing sector. A natural development from previous studies is to investigate the internationalization of service firms. Japanese Trading Companies (J-GTCs) are service companies actively involved in stronger internationalization. Several studies have investigated the internationalization of Japanese Multinational Enterprises (JMNEs) in the manufacturing sector. However, a still limited number of studies analyze the internationalization of JMNEs in the service sector, particularly J-GTCs. Given the lack of studies and the relevance of understanding the role of the ownership structure in access to international markets, the overall objective of this research is to analyze the impacts of the strategy tripod factors on the ownership structure of foreign subsidiaries of J-GTCs. Thus, this paper intends to contribute to the literature on the following points: (i) to identify which factors impact this ownership structure based on the strategy tripod; (ii) to verify how J-GTC size and experience influence internationalization strategies in terms of ownership structure. Four core hypotheses were developed to be empirically tested in a quantitative study to achieve these objectives. We used the most recent secondary database of Japanese overseas investments, Toyo Keizai - 2021, and applied multiple linear regression statistical techniques. The results showed that target market size and development level have a direct, positive relationship with ownership structure, whereas market growth and J-GTC size negatively affect ownership structure. The analysis of the relationship between the strategy tripod and ownership structure showed that the sector-based view (SBV) and the resource-based view (RBV) as concerns invested capital have a direct and positive relationship, whereas the level of local experience yielded a direct, but negative relationship. The institution-based view (IBV) showed no direct effect on the ownership structure. On the other hand, local experience moderates SBV and RBV by increasing J-GTCs’ equity interest in local businesses and decreasing it when the invested capital is higher. At the same time, international experience moderates SBV and IBV and increases equity interests in global businesses when there is greater formal and informal institutional distance. Therefore, this study contributes to a better understanding of J-GTCs’ internationalization strategy at the sector, resource, and institutional levels. It also provides an analysis that complements existing literature by showing that experience is an essential factor in shaping ownership structure, but with different impacts depending on the level of this experience. These findings may also assist managers in the internationalization process of service firms.